Effect of purified dust from CaC2 production and bottom ashes/slags on slagging characteristic of Zhundong coal blend. (15th October 2022) - Wang, Yibin; Li, Liangyu; Tan, Houzhang; An, Qiwei; He, Lihai; Sun, Rui; He, Guang; Yang, Jianwei
Graphical abstract: Highlights: Characterization of bottom ashes/slags (BAS) from a pulverized coal boiler was studied. BAS mainly contains SiO2, CaCO3 and Al2 O3 except for C element enrichment. Effect of fine/coarse BAS on slagging behavior of coal blend was studied. 5% fine BAS addition converted glassy slags at 1200℃ into low molten deposits. Different groups composed of BAS and PD inhibited the formation of more melting minerals. Abstract: Coal cofiring with carbon-containing solid wastes can achieve resource utilization and promote the circular economy development. This work aims to investigate the effects of C-rich bottom ashes/slags (BAS), fine/coarse BAS separated by mechanical sieving, and the mixture of untreated BAS with purified dust (PD) from CaC2 production acting as additive on slagging behavior and mineral phase transformation of Zhundong (ZD) coal blend. Detail characterizations including chemical composition, micro-morphology, mineral phases and weight loss of BAS were performed. The ash fusion tests for coal blend with varying proportions of additive were conducted. The compositional analyses of deposits on an un-cooled probe at different sampling temperatures (600/800/1000/1200 ℃) in a drop-tube furnace were investigated. The results show that three types of untreated BAS have similar physicochemical properties. The BAS addition has a negative influence on ash fusion temperatures, but they would completely change the types of crystal minerals in the melted deposits dominated by amorphous substance at 1200 ℃. The addition of 5 wt% coarse (>1 mm) or fine (<53 μm) BAS promotes glassy slags at 1200 ℃ converting into deposits with a low melt fraction, but the influence of fine BAS is more pronounced. A group composed of untreated BAS and PD at an appropriate ratio, promotes the formation of more crystal minerals with high melting points in deposits at 1200 ℃.